Informing BPM practice in Emergency Units of South African hospitals for improved patient flow - Loriston, Izienne P (Department of Information Systems, 2018)
Globally, higher healthcare demand strains existing systems, already overburdened by a lack of resources and funding while longer life expectancy and increased disease burden force higher patient loads. A majority of the South African population is medically uninsured and therefore depend on emergency care; consequently, the healthcare service demand easily exceeds available acute care to prevent life threat. When this happens, emergency centres suffer from overcrowding and long patient waiting times, which increases morbidity and mortality, associated patient risk. Moreover, critical resources such as staff and hospital beds are required for an even flow of patients through hospitals, but are distributed inefficiently. The South African healthcare system configuration therefore delays access to and compromises the delivery of equitable, unbiased life-saving healthcare in an environment moreover challenged by economic pressures. This calls for sustainable, cost-effective reform. Therefore, more efficient healthcare can save more lives by improving access to life-saving care. Research on current Healthcare Information Systems (HIS) shows an incoherent knowledge body with conceptual gaps in theories on healthcare, which disengages transformation potential. Comprehensive reform tactics thus require a priori concept discovery and diagnostics to make research practically useful. The systematic use of BPM theories allowed for the qualitative assessment of as-is process activity at patient touch-points at three hospitals – two public and one private – in the Western Cape of South Africa. Because a strategic Information Systems (IS) methodology, Business Process Management (BPM) poses business process activity improvement, this research draws from successful BPM activity as a means to improve patient flow processes in Emergency Centres (ECs). Success is evaluated by drawing from empirically supported enabler categories and prescriptive guidelines because BPM practice is not yet fully understood. The results show a clear correlation between the improvement areas at the three hospitals; improvements on aspects of actions and decisions taken during patient-flow process activity, therefore support a pragmatic approach to reform. The data confirms disparity between public and private healthcare. Healthcare appears to be a “doctor driven” service, which, based on qualitative decision-making, navigates patients along defined flows, enabled by supporting human capital and hospital assets. Optimal patient flow is a product of symbiotic working relationships and depends on efficient integration with wider hospital functions. Shorter waiting times and hospital stays reduce process burden. This leads to more efficient resource usage and regulated access to healthcare. However, integrated healthcare reform must consider the time demands and rigidity of clinical processes. The challenge lies in finding the space to invite parallel business agility to drive the reform of the stricken healthcare industry in South Africa.